2012
DOI: 10.1002/cphc.201200648
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Silica Supported Molybdenum Oxide Catalysts at Work: A Raman Spectroscopic Study

Abstract: The structure of silica SBA-15-supported molybdenum oxide catalysts is investigated during selective oxidation of propylene at 500 °C using operando Raman spectroscopy. The active catalysts contain mixtures of dispersed molybdenum oxide species exhibiting monooxo and dioxo structure. An increase in molybdenum oxide loading results in a decrease of the ratio of dioxo and monooxo species from 3.8 to 1.9, as determined by quantitative analysis of Raman spectra. Additional in situ Raman studies at 500 °C reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…25 Other authors have found an increase of monoxo/dioxo ratio in the Raman spectra of a MoO x /SiO 2 catalyst during propylene oxidation reaction. 26 Moreover, thanks to an operando Raman/IR investigation of methanol oxidation by Mo/Al 2 O 3 , further supported by a model TPR and H 2 /D 2 isotopic exchange, the existence of reduced Mo−O−H group on surface of catalyst after reduction was attested. 20 Furthermore, the authors have detected the presence of Mo V probed by in situ EPR spectroscopy after having subjected the same catalyst to a CH 3 OH/He flow.…”
Section: ■ Introductionmentioning
confidence: 89%
“…25 Other authors have found an increase of monoxo/dioxo ratio in the Raman spectra of a MoO x /SiO 2 catalyst during propylene oxidation reaction. 26 Moreover, thanks to an operando Raman/IR investigation of methanol oxidation by Mo/Al 2 O 3 , further supported by a model TPR and H 2 /D 2 isotopic exchange, the existence of reduced Mo−O−H group on surface of catalyst after reduction was attested. 20 Furthermore, the authors have detected the presence of Mo V probed by in situ EPR spectroscopy after having subjected the same catalyst to a CH 3 OH/He flow.…”
Section: ■ Introductionmentioning
confidence: 89%
“…In catalysis DRIFTS is appliedt o investigate the adsorptiono fr eactantso no rt he poisoning of the actives ites at the catalyst surface [29c, 43] and the restructuring of catalyst materials. [72] Demoulin et al [8g, 67] used in situ/operando DRIFTS to investigate chemical adsorbates, intermediates and products during the catalytic combustion of CH 4 with Pd/Al 2 O 3 catalysts. They proposed at wo-step reactionS cheme with aPd x 0 -CO species as important surface intermediate.…”
Section: Characterization and Operando Methodology In Gas Sensing Andmentioning
confidence: 99%
“…2,3,5,6,8,15,17,22−30 On this basis, there is strong evidence that under dehydrated conditions, the isolated surface Mo(VI) sites predominantly exist as four-coordinate dioxo Mo(VI) species, although minor five-coordinate monooxo Mo(VI) species can be also present (Figure 1). 3,5,6,14,[22][23][24][25]28 Besides the monomers, dimeric/oligomeric Mo(VI) oxide species or clusters at relatively low Mo loadings were sometimes suggested. 15,26,27 Crystalline MoO 3 is additionally observed for high Mo content.…”
Section: ■ Introductionmentioning
confidence: 99%